Utilizing Travel Vlogs to Boost Students’ Confidence in Speaking English: Tourism Students’ Perspective - Ningsih, Wirda; Rohliah, Leni; Lestari, Pratiwi; Hutagalung, Genta Ulina (International Journal of English Language and Pedagogy, 2023)
One of the challenges students face in learning English is the confidence to speak the language in practical situation. To cope with this problem, incorporating travel vlogs in English classroom may be one of the solutions. The purpose of this study is to examine and describe the students' perspective towards the use of travel vloggings in the English classroom and whether it can help boost their confidence in speaking English. This study was conducted at Sriwijaya State Polytechnic, participated by second semester students of Tourism Business Management department who took English for Tourism Industry compulsory subject. The data were collected using questionnaire and then analysed using qualitative descriptive approach. The results showed that students have positive attitude towards the use of travel vlogs to boost their confidence in speaking English.